2017
DOI: 10.1097/mpg.0000000000000563
|View full text |Cite
|
Sign up to set email alerts
|

A Challenging Case of Focal Extrahepatic Duct Obstruction/Hypoplasia in Alagille Syndrome

Abstract: In premature infants, adaptation of the bowel (including intestinal dilation and lengthening, growth of the villi, alterations of motility, and hormonal changes) is a important process that must be completed before adequate absorption of nutrients and weight gain can occur after intestinal surgery (2,5,6). Establishment of a high stoma can influence bowel adaptation and lead to various problems, such as fluid and electrolyte imbalance, abnormal acidbase status, nutritional deficiency/malnutrition, and specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Han et al ( 13 ) reported that the patent biliary tree of 3 infants with AGS was not presented by intraoperative cholangiography, resulting in a misdiagnosis of BA. Furthermore, 26 patients with AGS from six studies were misdiagnosed with BA and received KPE based on intraoperative cholangiography ( 14 16 , 30 32 ). Unfortunately, AGS exhibited considerable overlapping features with BA, leading to improper KPE and even worsening the patient’s outcome ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Han et al ( 13 ) reported that the patent biliary tree of 3 infants with AGS was not presented by intraoperative cholangiography, resulting in a misdiagnosis of BA. Furthermore, 26 patients with AGS from six studies were misdiagnosed with BA and received KPE based on intraoperative cholangiography ( 14 16 , 30 32 ). Unfortunately, AGS exhibited considerable overlapping features with BA, leading to improper KPE and even worsening the patient’s outcome ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…BA and AGS may be indistinguishable and pose diagnostic challenge for neonatal cholestasis. AGS can share biochemical, imaging, histological, and operative cholangiogram features with BA (23). Although genetic testing may help to differentiate the diseases, the results often take several weeks (>4 weeks) to return at a time when further delay in BA diagnosis and surgical intervention may compromise outcome.…”
Section: Discussionmentioning
confidence: 99%
“…BA screening using ISCC has been implemented in European and South American countries (15,16). ISCC screening has been reported to be highly feasible, effective, and cost-effective in both Taiwan and Japan (7,8,17,18) The Taiwanese national ISCC BA screening program, in place since 2004, has eliminated late BA referrals after 90 days of age with improved 5-year native liver survival (8). In the Tochigi Prefecture of Japan, where the stool color card was first developed and introduced in 1994 by Matsui, the native liver 5 and 10 year survival rates increased by >20% during 1994-2011 compared with other Japanese jurisdictions without an ISCC screening program (18).…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative cholangiography is considered the gold standard for diagnosing BA, but the method can be misleading in up to 20% of cases [ 7 , 46 , 47 , 48 , 49 ]. Pathophysiological considerations can help us understand why diagnostic errors occur in intraoperative cholangiography.…”
Section: The First Challenge: Pitfalls In the Diagnosis Of Biliary At...mentioning
confidence: 99%
“…Pathophysiological considerations can help us understand why diagnostic errors occur in intraoperative cholangiography. Extrahepatic bile flow blockage does not occur exclusively from complete mechanical obstruction caused by BA but also from extrahepatic bile duct hypoplasia caused by decreased intrahepatic bile flow, or extrahepatic bile duct agenesis both associated with Alagille syndrome [ 49 , 50 , 51 ]. Inadvertently submitting an infant with Alagille syndrome to a Portoenterostomy based on a false-positive diagnosis of BA can lead to grievous prognostic consequences [ 52 , 53 ].…”
Section: The First Challenge: Pitfalls In the Diagnosis Of Biliary At...mentioning
confidence: 99%